2018
DOI: 10.1089/ten.tea.2017.0449
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Dimensional Human Tissue-Engineered Lung Model to Study Influenza A Infection

Abstract: Influenza A virus (IAV) claims ∼250,000-500,000 lives annually worldwide. Currently, there are a few in vitro models available to study IAV immunopathology. Monolayer cultures of cell lines and primary lung cells (two-dimensional [2D] cell culture) is the most commonly used tool, however, this system does not have the in vivo-like structure of the lung and immune responses to IAV as it lacks the three-dimensional (3D) tissue structure. To recapitulate the lung physiology in vitro, a system that contains multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 81 publications
4
65
0
Order By: Relevance
“…For example, Bhowmick et al created a 3D chitosan-collagen scaffold polymerized on top of a Transwell insert membrane before culturing human small airway epithelial cells on top of this scaffold and airlifting (exposing to air) the model. When compared to a non-3D scaffold control, they found differences in protein expression in uninfected, H1N1, and H3N3 flu virus-infected epithelial cells (243). These results suggest that the addition of ECM components makes a difference in cellular functions.…”
Section: Transwell Models For Studying Pathogenic Infectionmentioning
confidence: 94%
See 1 more Smart Citation
“…For example, Bhowmick et al created a 3D chitosan-collagen scaffold polymerized on top of a Transwell insert membrane before culturing human small airway epithelial cells on top of this scaffold and airlifting (exposing to air) the model. When compared to a non-3D scaffold control, they found differences in protein expression in uninfected, H1N1, and H3N3 flu virus-infected epithelial cells (243). These results suggest that the addition of ECM components makes a difference in cellular functions.…”
Section: Transwell Models For Studying Pathogenic Infectionmentioning
confidence: 94%
“…Building upon these simpler systems, advanced models have also been developed that incorporate a three-dimensional culture into a Transwell insert-based platform. These models often include other tissue features such as an ECM/stromal component (189,243) and immune components (189). For example, Bhowmick et al created a 3D chitosan-collagen scaffold polymerized on top of a Transwell insert membrane before culturing human small airway epithelial cells on top of this scaffold and airlifting (exposing to air) the model.…”
Section: Transwell Models For Studying Pathogenic Infectionmentioning
confidence: 99%
“…Many works in the literature reported comparative studies of monolayer cells and 3D cultures infected with different types of viruses, such as poxviruses [ 51 , 52 ], adenovirus [ 53 ], hepatitis B and C [ 53 , 54 ], Zika [ 15 , 55 ] and influenza [ 10 ]. These works showed that different approaches of 3D cell culture, such as spheroids, organoids, 3D scaffolds and bioprinted structures were able to mimic many types of tissues using different cell lines, presenting higher sensitivity in virus isolation and specificity of several antiviral compounds than conventional 2D models.…”
Section: Vs 3d In Vitro Models In Virologymentioning
confidence: 99%
“…With the advances of tissue engineering, novel technologies have emerged and been used as more realistic in vitro models, allowing the construction of complex cytoarchitecture, with better representation of cell heterogeneity, extracellular matrix (ECM) composition, and functionality of native tissues [ 9 ]. 3D in vitro models consist of scaffold-free (spheroids and organoids) or scaffold-based (3D scaffolding and 3D bioprinting) systems used to study infectivity, replication kinetics, and host-viral interactions of many types of viruses, such as influenza [ 10 , 11 ], syncytial [ 12 ], adenovirus [ 13 ], norovirus [ 14 ], Zika [ 15 ], and more recently, SARS-CoV-2 [ 16 ], showing increased physiological relevance as compared to 2D models.…”
Section: Introductionmentioning
confidence: 99%
“…31 For example, in a model to study influenza A virus, 3D tissueengineered constructs more accurately recapitulated the host morphology of cultured human epithelial airway cells compared to 2D culture, and infection with major influenza strains resulted in upregulation of proinflammatory cytokines. 32 One coronavirus-specific example of a tissueengineered platform in which respiratory viruses have been studied is the rotation wall vessel bioreactor. These models simulate low physiologic shear stresses and frequently incorporate multiple pulmonary cell types, including coculture of human mesenchymal bronchial tracheal cells and human bronchial epithelial cells, challenging them against respiratory syncytial virus and SARS-CoV-1.…”
Section: In Vitro Modelsmentioning
confidence: 99%